Multidrug-Resistant Hypervirulent Klebsiella pneumoniae Found Persisting Silently in Infant Gut Microbiota - I. Y. Vasilyev; I. V. Nikolaeva; M. N. Siniagina; A. M. Kharchenko; G. S. Shaikhieva (International Journal of Microbiology)
Since the spread of multidrug-resistant Klebsiella pneumoniae (MDRKP) strains is considered as a challenge for patients with weakened or suppressed immunity, the emergence of isolates carrying determinants of hypervirulent phenotypes in addition may become a serious problem even for healthy individuals. The aim of this study is an investigation of the nonoutbreak K. pneumoniae emergence occurred in early 2017 at a maternity hospital of Kazan, Russia. Ten bacterial isolates demonstrating multiple drug resistance phenotypes were collected from eight healthy full-term breastfed neonates, observed at the maternity hospital of Kazan, Russia. All the infants and their mothers were dismissed without symptoms or complaints, in a satisfactory condition. Whole-genome shotgun (WGS) sequencing was performed with the purpose to track down a possible spread source(s) and obtain detailed information about resistance determinants and pathogenic potential of the collected isolates. Microdilution tests have confirmed production of extended-spectrum β-lactamases (ESBL) and their resistance to aminoglycoside, β-lactam, fluoroquinolone, sulfonamide, nitrofurantoin, trimethoprim, and fosfomycin antibiotics and Klebsiella phage. The WGS analysis has revealed the genes that are resistant to aminoglycosides, fluoroquinolones, macrolides, sulfonamides, chloramphenicols, tetracyclines, and trimethoprim and ESBL determinants. The pangenome analysis had split the isolates into two phylogenetic clades. The first group, a more heterogeneous clade, was represented by 5 isolates with 4 different in silico multilocus sequence types (MLSTs). The second group contained 5 isolates from infants born vaginally with the single MLST ST23, positive for genes corresponding to hypervirulent phenotypes: yersiniabactin, aerobactin, salmochelin, colibactin, hypermucoid determinants, and specific alleles of K- and O-antigens. The source of the MDRKP spread was not defined. Infected infants have shown no developed disease symptoms.